Francesco Venezia - L’azione del tempo - Marzo, Mauro (Firenze Architettura, 2018)
The representation of the passage of time is a theme that pervades the works of Francesco Venezia, his writings, teachings and projects. Comparing distant works such as his intervention on the underground spaces of the cathedral of Caserta and the Material Testing Lab in Mestre, offers the opportunity of an in-depth analysis of this question through the methods and design choices adopted for the two different contexts.